2016
DOI: 10.1080/07294360.2016.1176997
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing impact in academic development: finding a way through

Abstract: This paper explores the notion of impact in the context of academic development programs and considers how it can be described and understood. We argue that impact has a range of meanings and academic development programs such as graduate certificates have a broad group of stakeholders and hence the impact is different for each group depending on how the program aims and objectives are defined and understood. In finding a way through the difficulties of evaluating impact in academic development we point to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…With an estimated workload of 300 h, the majority of hours were self-study, as only ten face-to-face group meetings of 2-3 h with a professional coach were arranged. Previous studies (Rienties and Kinchin, 2014;Rienties and Hosein, 2015;Jones et al, 2017) have found that this PD program was considered to be valuable to participants in terms of enhancing their teaching and learning practice, network formation, and social support. Furthermore, qualitative follow-up analyses (Rienties and Hosein, 2015) indicated that PD participants primarily relied on their PD peers in terms of academic, professional, and emotional support to make sense of the program, as well as to learn from their peers how to critically reflect on their own teaching and learning practice.…”
Section: Settingmentioning
confidence: 99%
“…With an estimated workload of 300 h, the majority of hours were self-study, as only ten face-to-face group meetings of 2-3 h with a professional coach were arranged. Previous studies (Rienties and Kinchin, 2014;Rienties and Hosein, 2015;Jones et al, 2017) have found that this PD program was considered to be valuable to participants in terms of enhancing their teaching and learning practice, network formation, and social support. Furthermore, qualitative follow-up analyses (Rienties and Hosein, 2015) indicated that PD participants primarily relied on their PD peers in terms of academic, professional, and emotional support to make sense of the program, as well as to learn from their peers how to critically reflect on their own teaching and learning practice.…”
Section: Settingmentioning
confidence: 99%
“…The rationale for research impact frameworks, at least in OECD countries, also appears to be centred, narrowly, on allocating finance (see discussion in Jones et al 2017). This can be seen, for example, in moves by some government bodies to include, as a condition of funding, provision that research has a proven effect outside the university environment.…”
Section: Traditional Categories Of Research Impact and Recent Frameworkmentioning
confidence: 99%
“…see Marcella, Lockerbie, and Cameron 2015; Watermeyer 2016) impact measurements, identified through post-research publications (and citations for the academic impact), and policy changes, at wide spatial levels, with little measurement of behavioural impacts and collaborative influence generated through processes of conducting the research itself. Additionally, there is often a focus on economic rather than societal effects when measuring these impacts (e.g., Jones et al 2017;Mullins 2015).…”
Section: Introductionmentioning
confidence: 99%
“…administrativt ansatte blir tildelt ansvar for å strukturere studieprogram som kan passe inn i kvalitetssystemenes rapporteringslogikk, skaper dette potensielt nye spenninger mellom administrative og faglige interesser. Studenter, vitenskapelig ansatte, og vitenskapelige så vel som administrative ledere, har ofte ulike oppfatninger om hva «kvalitet» er, og hva UH-pedagogisk virksomhet skal vektlegge (Jones et al 2017).…”
Section: Uh-pedagogikkens Profesjonelle Og Komplekse Samfunnsmandatunclassified